DEVELOPMENT OF MATHEMATICS LEARNING MEDIA ON ALGEBRAIC FORMS USING A SIMPLE APPLICATION WITH MIT APP INVENTOR - Marisa Ayu Priyandani; Reza Kusuma Setyansah (Penelitian dan Pengembangan Ilmu, 2025)
This research focuses on the development of interactive learning media for algebraic mathematical materials using a simple application MIT App Inventor. The concept of algebraic forms is often challenging for students due to its abstract nature, so innovative and engaging media are needed to facilitate understanding. The purpose of developing this media is to provide a tool that can increase student learning motivation and understanding of the basic elements of algebra. The application developed with MIT App Inventor is equipped with interactive features such as concept simulations, practice questions, and instant feedback designed to help students master arithmetic operations, identification of variables, coefficients, and constants in algebraic forms. The development results show that this interactive learning media has high validity and practicality, and has the potential to increase student engagement and learning outcomes in algebraic forms. This media is expected to be an effective alternative learning resource for teachers and students in the mathematics learning process.